2000
DOI: 10.1053/jvet.2000.5603
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Results of Bovine Mandibular Fractures Involving the Molar Teeth

Abstract: Mandible fractures involving the molar teeth carry a good prognosis for return to normal function. Radiographic follow-up is necessary to detect bone sequestration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
(5 reference statements)
3
3
0
Order By: Relevance
“…Consequently, they have a high rate of infection and are prone to sequestration. Our results are in agreement with the outcome of 2 retrospective studies 2,8 where sequestration was reported to be a common complication after mandibular fracture repair in horses and cattle. Fixation techniques included use of DCP, U‐bar, wiring, and PEF 2,8 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consequently, they have a high rate of infection and are prone to sequestration. Our results are in agreement with the outcome of 2 retrospective studies 2,8 where sequestration was reported to be a common complication after mandibular fracture repair in horses and cattle. Fixation techniques included use of DCP, U‐bar, wiring, and PEF 2,8 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in agreement with the outcome of 2 retrospective studies 2,8 where sequestration was reported to be a common complication after mandibular fracture repair in horses and cattle. Fixation techniques included use of DCP, U‐bar, wiring, and PEF 2,8 . However after fixation with LCP in 6 cases, no sequestration occurred even though several fractures were severely comminuted and infected 3 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The slight bone reabsorption around pins and a moderate periosteal bone reaction, suggest that the stability of the implant was adequate for all the bone healing time despite the non-anatomical reduction of the fracture gap. The osseous sequestrum and osteomyelitis have been reported in fragmented bovine mandibular fractures, treated with an AO/ASIF-Pinless External Fixators (Reif et al, 2000). In our case the clinical and radiographic follow-up, despite the bilateral fragmentation, did not show signs of complications.…”
Section: Discussionsupporting
confidence: 47%
“…In cattle, the AO/ASIF pinless ESF system has been used successfully in the treatment of mandibular fractures (Lischer et al . 1997a,b; Reif et al . 2000).…”
Section: Discussionmentioning
confidence: 99%